Managing the complexity through new forms of financial reporting: A multiple case study on Italian public museums - Virginia Milone; Simone Pizzi (Administrative Sciences, 2019)
During recent years, an increasing number of studies have started to discuss the introduction of new form of reports in public administration. Furthermore, the attention paid by academics has been favoured by the introduction of a new form of regulation by policy makers. Specifically, a large part of these studies has regarded the heritage sector due to its high degree of complexity. The attention paid to the heritage sector has been driven by the existence of asymmetries between the value of cultural assets and the profitability of institutions. According to this evidence, the aim of this paper is to evaluate the effectiveness of the Italian Integrated Economic Report (IER). Our research highlights that the adoption of managerial reports, such as the IER, could provide useful insights for policy makers in order to invest their financial resources in a more effective way.
Keywords: 350; museums; heritage management; reporting; state owned enterprises